(untitled) (Scientific journal of the Fergana State University, 2023)
The article presents information about the mythologicalization of mythological images in English and Uzbek literature and their specific features. It is known that myths play a very important role in the world literature. In the literature of all nations, myths, legends and fairy tales embody the way of life and characteristics of the nation. Mythological images have been widely used for centuries in the English and Uzbek oral and written literature. From ancient English and Uzbek literature to the literature of the modern period, there can be met mythologicalization process of mythological images that reflect the literary connection and interaction between the literatures of the two nations.